Model Bimbingan Dalam Pendidikan Agama Kristen Terhadap Pembentukan Moral Anak Didik Usia 6-8 Tahun - Eliman Eliman (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2017)
The child needs to be educated to be guided for moral value. If child doesn’t get education and guidance for the proper moral value, the kid will not be able to be controlled immoral and got worst and the kid can be a criminal and community destroyer. The guidance for the kid’s moral value is an aspect which need to be considered seriously and can’t be abandoned. The improvement of the kid’s moral value need to be known not only those which explain by the expert but also those which stated in bible about the improvement of kid’s moral value so the teacher and parents can guide the kid in the correct moral value. 6 to 8 years old kid is elemantary level kid, the age that can receive other people otority beside the parents and obey the rules. 6 to 8 years old is the period of improvement or the process of maturity , with the education and guidance to the  kid will be easy to be absorb and receive by the kid.